Correlation Analysis of Galectin-3 Serum Level in Obesity with and without Obesity - Nurjannah Nurjannah; Nurahmi Nurahmi; Liong Boy Kurniawan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
There are more than 3.4 million deaths every year in the world due to overweight and obesity. Obesity is a chronic proinflammatory condition marked by increased lipid and adipose tissues, leading to ectopic fat accumulation with increased levels of proinflammatory cytokines. Obesity causes a progressive increase in galectin-3 expression, especially in visceral and subcutaneous adipose tissue in experimental animals. Galectin-3 is upregulated in obesity and is defined as a proinflammatory molecule that can cause insulin resistance. This study aims to analyze differences in galectin-3 levels between obese and non-obese subjects. This was a cross-sectional study, using a total of 80 subjects. The study was conducted throughout August 2022. The samples were grouped into obese and non-obese based on Body Mass Index (BMI). The galectin-3 measurement used the Enzyme-Linked Immunosorbent Assay (ELISA) method. Statistical tests used the Mann-Whitney test and Spearmen rho; the test results were significant if the p-value <0.05. The samples were divided into obese and non-obese groups, each group had 40 people. Galectin-3 levels in the obese group were 0.9±0.36 ng/mL significantly higher than the non-obese group’s 0.43±0.11 ng/mL, (p<0.001). There was a strong positive correlation between levels of galectin-3 and BMI, (r=0.866, p<0.001). There is a positive correlation between serum galectin-3 levels and BMI. The greater value of the BMI, the higher levels of galectin-3.